Evaluasi Oral Antidiabetik Pada PAsien Diabetes Melitus Tipe 2 Di RSUD "X" Lamongan - bintang, sri; Utami, Primanitha Ria; Amala, Siti Nur (Journal of Herbal, Clinical and Pharmaceutical Science (HERCLIPS), 2020)
Diabetes Mellitus Type 2 is a metabolic disorder characterized by an increase in blood sugar due to decreased insulin secretion by pancreatic beta cells and or insulin function disorders (insulin resistance). This study aims to evaluate oral antidiabetics in patients with type 2 diabetes mellitus at the Regional General Hospital dr. Soegiri Lamongan. This research design is descriptive with a population of all type 2 diabetes mellitus patients from July to August 2019 using a total sampling technique. The number of samples in this study were 64 patients. The results showed that the most prescribed oral antidiabetic in type 2 diabetes mellitus patients at the RSUD in Lamongan was an oral combination of antidiabetic, namely Gliclazid and Metformin (29.70%), in terms of the correct dose and method of administration of the drug, in accordance with the guidelines in the Ministry of Health. and FRS (100%), in the data of patients who experienced a decrease in GDA, it was seen that the combination therapy of sulfonylurea and biguanide compared to single therapy was 92.5%. Keywords: Diabetes Mellitus Type 2, Oral Antidiabetic, Blood Glucose